TERAPI FINGOLIMOD PADA MULTIPEL SKLEROSIS BENTUK HIGHLY ACTIVE - Riwanti Estiasari,* Sari Nurul Hanifa,* Reyhan Eddy,** Birry Karim*** (Neurona Majalah Kedokteran Neuro Sains, 2016)
THIS CASE REPORT WE DESCRIBE A CASE OF HIGHLY ACTIVE MULTIPLE SCLEROSIS MS IN WOMEN AGED 41 YEARS HER COMPLAINT WAS WEAKNESS ON HER BOTH LEGS AND IMPAIRMENT OF COORDINATION FUNCTION IT BECAME WORSE IN THE LAST 1 YEAR